The Meaning of Endeavor and Trust in the Novel Hajar the Secret of the Queen's Heart Zamzam a Perspective on the Hadith - Purwanto, Shinta Ratu Putri Unon; Anwar, Latifah (Universitas Ibn Khaldun, 2025)
Humans sometimes have feelings that change according to the situation and conditions they are facing. Every human being has different traits and attitudes, this is what causes a person to have various actions when controlling his emotions. One of the human beings who can be exemplified in responding to things calmly and patiently is Siti Hajar. When faced with a test, he tends to accept and live it as much as possible to the limit of his ability and always involve God in every effort. In Islam, it is called effort and tawakal. The purpose of this research is to provide a deeper understanding of efforts and tawakal, especially through hadith and how it is represented in the novel